2012
DOI: 10.1186/1476-9255-9-13
|View full text |Cite
|
Sign up to set email alerts
|

A panel of oxidative stress assays does not provide supplementary diagnostic information in Behcet's disease patients

Abstract: BackgroundRecent findings suggest a role of oxidative stress in the pathogenesis of Behcet's disease (BD), but the utility of oxidative stress-associated assays in offering diagnostic information or in the monitoring of disease activity is largely unassessed.Objective and methodsWe aimed to measure oxidative and inflammatory markers, along with the markers of reactive nitrogen species, S-nitrosothiols and 3-nitrotyrosine, in BD patients (n = 100) and healthy volunteers (n = 50). These markers were evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…In humans, a correlation between TOS e NO x levels was also shown (Padhy et al, 2015), whereas in our study the correlation was not observed (r = 0.370; p = 0.10). NO x levels were also significantly correlated with TAA, as well as MPO activity with TAC, as previously shown in human disorders, in which the increased NO x levels and MPO activity are suspected to be involved in OS (Akcay et al, 2012;Schuh et al, 2018).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In humans, a correlation between TOS e NO x levels was also shown (Padhy et al, 2015), whereas in our study the correlation was not observed (r = 0.370; p = 0.10). NO x levels were also significantly correlated with TAA, as well as MPO activity with TAC, as previously shown in human disorders, in which the increased NO x levels and MPO activity are suspected to be involved in OS (Akcay et al, 2012;Schuh et al, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…Although both ROMs and TOS assays are based on iron-mediated mechanisms, the principles of detection are quite different, and this could be the reason for the lack of correlation (Erel, 2005;Jansen and Ruskovska, 2013). In reality, the ROM test, given by Alberti et al (2000) as a specific measurement of hydroperoxide levels, was correlated neither with TOS nor MPO in the present results. In contrast, a highly significant correlation with CP oxidase activity, a glycoprotein known as a potent physiologic inhibitor of myeloperoxidase (Chapman et al, 2013), was evidenced in goat sera.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…[8][9][10] Various oxidative stress markers and oxidative states have also been studied in patients with BD with inconsistent results. [11][12][13] Oxidative stress and inflammatory processes are the main features of many acute and chronic diseases, such as cancer, lung disease, cardiovascular disease, and rheumatic disease, as well as normal aging processes.…”
Section: Introductionmentioning
confidence: 99%